PROPOSED MARKETING STRATEGY FOR CICIL EMAS MULIA AT PT PEGADAIAN - Sulaiman, Ibnu
This research is conducted to address issues occurring at PT Pegadaian. The first chapter explains how Cicil Emas Mulia by Pegadaian, as a financing product, faces challenges related to the realization of its sales targets. The sales realization of Cicil Emas Mulia fluctuates from year to year. Pegadaian gold installment product sales should also have increased in line with the development of investment preferences. In fact, until September 2023, it is still far below the annual target and the gap between realization and target is very far at 61%. This gap between sales target and actual realization needs immediate attention as a critical business issue. In the second chapter, the discussion revolves around the literature review, encompassing the theoretical foundation and conceptual framework related to problem resolution. In the third chapter, the explanation focused on how the research methodology was conducted, including the development of the research design, methods of data collection, and data analysis. Primary data was collected qualitatively for the analysis of STP, Marketing Mix, Resources, and Value Chain Activities, and quantitatively for Consumer Analysis through a survey questionnaire. Meanwhile, secondary data was collected qualitatively for the analysis of PESTLE, Competitor Analysis, and Industry Analysis. Data analysis was carried out using the Normality Test and Mean Difference Test with SPSS, while the validity test, reliability test, and path analysis were conducted using SmartPLS.